2022
DOI: 10.1021/acscatal.2c00905
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Surface-Sensitive Investigation of Multiple Carbon Phases on Fe(110) in the Fischer–Tropsch Synthesis

Abstract: Carbide formation on iron-based catalysts is an integral and, arguably, the most important part of the Fischer− Tropsch synthesis process, converting CO and H 2 into synthetic fuels and numerous valuable chemicals. Here, we report an in situ surface-sensitive study of the effect of pressure, temperature, time, and gas feed composition on the growth dynamics of two distinct iron−carbon phases with the octahedral and trigonal prismatic coordination of carbon sites on an Fe(110) single crystal acting as a model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…It should be mentioned that a few tens of atomic layers in Febased catalysts have been characterized by surface-sensitive techniques recently. Shipilin et al 9 observed the coexistence of TP-and Oct-carbides on an Fe(110) single-crystal surface at various temperatures and gas compositions (e.g., at 548 K (H 2 / CO = 4) or 485 and 506 K (H 2 /CO = 1 and 2) from 85 to 700 mbar) by C 1s XPS, while only Fe 3 C (TP carbide) can be detected by surface XRD at 623 K and 150 mbar (H 2 /CO = 4). This nding supports that TP-and Oct-carbides can grow upon each other, which is in agreement with our theoretical model for the active site-the active site on the reconstructed surface may well be different from that derived from dominant FeC x bulk phases.…”
Section: Fec X Active Sites In Composite Fts Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that a few tens of atomic layers in Febased catalysts have been characterized by surface-sensitive techniques recently. Shipilin et al 9 observed the coexistence of TP-and Oct-carbides on an Fe(110) single-crystal surface at various temperatures and gas compositions (e.g., at 548 K (H 2 / CO = 4) or 485 and 506 K (H 2 /CO = 1 and 2) from 85 to 700 mbar) by C 1s XPS, while only Fe 3 C (TP carbide) can be detected by surface XRD at 623 K and 150 mbar (H 2 /CO = 4). This nding supports that TP-and Oct-carbides can grow upon each other, which is in agreement with our theoretical model for the active site-the active site on the reconstructed surface may well be different from that derived from dominant FeC x bulk phases.…”
Section: Fec X Active Sites In Composite Fts Catalystsmentioning
confidence: 99%
“…1 The reaction is operated at high temperature (423-623 K) and high pressure (2-3 MPa, H 2 /CO = 1-2) 2-5 using iron oxides or/and hydroxides as the catalysts that are in situ activated under a reductive gas ow for 2-24 h. The catalytic active phase has been long believed to be pertinent to complex carboncontaining Fe phases, i.e. iron-carbides (FeC x ), [6][7][8][9][10] where at least ve bulk phases with different Fe : C ratios and two different Fe-C local coordination patterns were reported, [11][12][13][14][15][16][17] namely triangular prismatic (TP) coordination for q-Fe 3 C, c-Fe 5 C 2 and Fe 7 C 3 phases and the octahedral (Oct) coordination for 3-carbides, 3 ′ -Fe 2.2 C, and 3-Fe 2 C. Despite the great importance of Fe-based FT technology and more than a century of research, it remains largely elusive on where and how the longchain hydrocarbons grow under the reaction conditions. New techniques are called for to clarify the in situ catalyst structural evolution and its dynamic coupling with FT reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Operando XPS probing the surface of Rh and Fe during CO hydrogenation reactions in the pressure regime 150–700 mbar has recently revealed important insights on ethanol synthesis 20 and Fischer–Tropsch synthesis of hydrocarbons. 21 The operando XPS will offer to provide insights into the nature of the catalyst and reaction intermediates for new catalyst development as is necessary for a non-fossil based chemical industry…”
Section: Probing Active Phase Of Catalyst By Operando Xpsmentioning
confidence: 99%
“…Blomberg et al showed the potential of this instrument to explore a wide pressure range, obtaining a global picture of the pressure dependence of surface species, products and intermediates, in a Pd(100) surface during CO oxidation with diluted gases [23]. More recently, other reactions of high practical interest, like the Fisher-Tropsch reaction on Fe(110) and the CO2 hydrogenation on Zn/ZnO/Cu(211) have been addressed [24][25].…”
Section: Recent Advances In Apxps For Heterogeneous Catalysismentioning
confidence: 99%